PERBEDAAN DERAJAT KESEHATAN GIGI DAN MULUT PADA SISWA SD DENGAN PROGRAM UKGS AKTIF DAN TIDAK AKTIF DI WILAYAH KERJA PUSKESMAS DENPASAR UTARA II TAHUN 2015 - I Nyoman Wirata (Poltekkes Kemenkes Jakarta III, 2016)
School aged students are oral health susceptible group because the 6 – 12 aged children are mixed dentition period that occur change from deciduous teeth topermanent teeth. The purpose of this study is to know the differences of students’ oral health level between active UKGS with non active UKGS in elementary schools at puskesmas II Denpasar Utara in 2015.The sample school used 2 as sample that were took by purposive sampling from 19 elementary schools thathave UKGS program which of of Puskesmas II Denpasar Utara’ working area. There is only one elementary school that have active UKGS. This observational study with cross sectional design use 186 students as sample from both schools and analyzed by MannWhitney-test. Results showed that the students’ oral hygiene and DMF-T scores at elementary school that have active UKGS with non active UKGS in which of Puskesmas II Denpasar Utara’ working area have different significantly for each (p<0,05). Conclusion of this study is the oral health level of students at elementary school that have active UKGS are better than non active UKGS one. Dental school program in elementary schools should be given regularly by teachers holders UKGS program so that elementary students havethe attitude, knowledge and behavior about oral health was good